(untitled) (Bangladesh Journal of Neuroscience, 2013)
A 40 years old man presented with progressive weakness and distal paraesthesia of limbs with difficulty in walking for last seven years. As the patient was not investigated thoroughly, a diagnostic dilemma was persisted. This patient went abroad & investigated thoroughly and yet not reached to a confirm diagnosis. Subsequently this patient reported to us and diagnosed it to be a case of Idiopathic Chronic Inflammatory Demyelinating Polyradiculoneuropathy (CIDP) responded to oral steroid therapy. After follow-up, this patient showed marked improvement. So diagnostic dilemma that persisted with such a patient that showed improvement with treatment and a challenge to a treatable condition had encouraged us to report the case. DOI: http://dx.doi.org/10.3329/bjn.v28i2.17185 Bangladesh Journal of Neuroscience 2012; Vol. 28 (2): 132-140